Report of the Steering Committee for Formulation of Ninth Plan (1997-2002) on Early Childhood Education (Formal) Non-Formal Education Secondary Education Vocational Education Distance Education Adult Education - Planning Commission (Planning Commission, 1998)
The report on education policies for India’s Ninth Five-Year Plan (1997-2002) outlines strategic measures to enhance the quality, access, and equity of education across all levels. Key priorities include universalizing primary education, improving secondary and vocational education, expanding adult literacy initiatives, and integrating early childhood development programs with health and nutrition. Emphasis is placed on gender equity, reducing disparities among disadvantaged groups, and fostering community and NGO participation. Financial allocations are increased to strengthen infrastructure, teacher availability, and program effectiveness, with particular focus on rural regions. The Working Group on Adult Education proposes actionable recommendations to integrate adult education with broader developmental objectives, harness technology, and decentralize program management. Overall, the plan presents a comprehensive framework to create an inclusive, efficient, and equitable education system aimed at supporting India’s socio-economic development.
Education Division Planning Commission January 1998
Education Division Planning Commission
Keywords: Education Policy; Ninth Five-Year Plan; Adult Education; Secondary Education; Early Childhood Education; Vocational Training; Literacy Campaigns; Gender Equity; Community Participation; Educational Infrastructure